(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2018)
Siphovalvulina is among the first foraminifera that appear on carbonate platforms of the Lower Jurassic, forming a conspicuous element of low-diversity assemblages prior to recovery after the end-Triassic biotic crisis. The high morphologic variability of species of this genus is usually not documented, which makes the determination of species difficult and subjective. We demonstrate the variability in five morphotypes of Siphovalvulina in Sinemurian and Pliensbachian carbonate rocks from the Dinarides and the Southern Apennines. Due to the different interpretation of its architecture, an emendation of the genus Siphovalvulina is proposed. One morphotype has been left in open nomenclature and could belong to either S. variabilis Septfontaine or to S. beydouni BouDagher-Fadel & Noujaim Clark. Three morphotypes, differing in apical angle and/or size belong to S. ex gr. gibraltarensis BouDagher-Fadel, Rose, Bosence & Lord. We also describe a new genus and species, Radoicicina ciarapicae gen. n., n. sp. from the lower Sinemurian of the Southern Apennines. We suggest a close phylogenetic relationship between the two genera and introduce a new family, Siphovalvulinidae fam. n. of the superfamily Eggerelloidea.